Oral health care behaviour in the society - Kurniawan, Gladys; Muhibat, Sjazili; Yubiliana, Gilang (Padjadjaran Journal of Dentistry, 2015)
Introduction: Behavior has an important role to determine the status of oral health. To form a behavior, we should have knowledge followed by a response in the attitude and ended by an action towards it. The aim of this study was to determine the society’s knowledge, attitude, and action to form society’s behavior towards the maintenance of oral health in Lebakgede Village Coblong Sub District, Bandung. Methods: This study was a descriptive study with approach a Cross-Sectional method and survey technique. The samples were taken by Multi-Stage Cluster Random Sampling with a sample size of 65 people between 15 and 49 years old. Results: The result shows that society’s knowledge was 78,5%, attitude was 98,5%, action was 72,3%, and behavior towards the maintenance of oral health in Lebakgede Village Coblong Sub District, Bandung was 90,8%. Conclusion: All society’s knowledge, attitude, action, and behavior towards the maintenance of oral health in Lebakgede Village Coblong Sub District, Bandung was good.